2005
DOI: 10.1055/s-2005-870246
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Diagnostic Tool for Detecting Functional Patency of the Small Bowel: the Given Patency Capsule

Abstract: This feasibility study has shown that the Given patency capsule is a safe, effective, and convenient tool for assessment of functional patency of the small bowel. It can indicate functional patency even in cases where traditional radiology indicates stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 10 publications
1
81
0
4
Order By: Relevance
“…A prospective, multi-center trial was designed to assess the clinical usefulness and safety of the PC capsule in patients with intestinal strictures suspected from clinical and/or radiological data. The global data of this trial have not been published, but the results of four of these centers have been reported (Table 1) [24][25][26][27] . In the series reported by Spada et al [24] , 30 out of 34 (88.2%) patients with known or suspected small bowel stricture retrieved the capsule in the stool.…”
Section: Clinical Trials With Patency Capsulementioning
confidence: 99%
See 1 more Smart Citation
“…A prospective, multi-center trial was designed to assess the clinical usefulness and safety of the PC capsule in patients with intestinal strictures suspected from clinical and/or radiological data. The global data of this trial have not been published, but the results of four of these centers have been reported (Table 1) [24][25][26][27] . In the series reported by Spada et al [24] , 30 out of 34 (88.2%) patients with known or suspected small bowel stricture retrieved the capsule in the stool.…”
Section: Clinical Trials With Patency Capsulementioning
confidence: 99%
“…The global data of this trial have not been published, but the results of four of these centers have been reported (Table 1) [24][25][26][27] . In the series reported by Spada et al [24] , 30 out of 34 (88.2%) patients with known or suspected small bowel stricture retrieved the capsule in the stool. After the excretion, the PC was intact in 20 cases (median transit time 22 h), and disintegrated in 10 patients (median transit time 53 h).…”
Section: Clinical Trials With Patency Capsulementioning
confidence: 99%
“…The patency capsule [11] is composed of lactose, remains intact in the gastrointestinal tract for 40-100 h post-ingestion, and disintegrates thereafter. Spada et al [12] have reported that 94% (30/34) of cases with small bowel stricture passed the intact or disintegrated capsule in the stools. Expulsion was confirmed in three cases by fluoroscopy, and the remaining patient withdrew consent to the study.…”
Section: Discussionmentioning
confidence: 99%
“…The patency capsule (PC) is a new nonendoscopic dissolvable capsule to check the patency of the digestive tract in a noninvasive manner. PC seems to be a useful noninvasive tool to identify which patients with suspected strictures could safely ingest the standard CE Banerjee et al 2007;Spada et al 2007;Signorelli et al 2006;Spada et al 2005].…”
Section: Diagnosis and Treatment Of Mgibmentioning
confidence: 99%